Navigating cultural autonomy: A critical analysis of governance in East Java Provincial Regulation Number 6 of 2024 concerning the advancement of regional culture - Andrean Caspari; M. Roehman Zainur Riedho; Salismi Zulfi Maulidita (Faculty of Social and Political Sciences, Universitas Diponegoro, 2025)
This study critically analyzes how East Java Provincial Regulation (Perda) No. 6 of 2024 structures cultural governance, evaluating its potential for participatory, inclusive, and sustainable cultural advancement. Employing a qualitative Critical Policy Analysis (CPA) of the full official text of the Perda and related documents, the research involved Content Analysis and Critical Discourse Analysis. Results demonstrate the Perda establishes a comprehensive legal and strategic framework by adopting national cultural paradigms, mandating the formation of a Regional Cultural Council (DKD), and emphasizing Regional Cultural Core Thoughts (PPKD) for strategic direction, with the Provincial Government playing a central regulatory role while normatively enshrining community participation. However, the CPA reveals that while detailed strategies are outlined, the practical realization of genuinely participatory mechanisms beyond formal councils, explicit operational coordination protocols, and precise funding allocations are largely deferred to a subsequent, all-encompassing Governor's Regulation. The study concludes that while the Perda provides a more robust and detailed foundation than initially assessable, its ultimate efficacy in fostering effective, inclusive, and sustainable cultural governance hinges critically on the substance, quality, participatory formulation, and accountable implementation of this forthcoming Governor's Regulation.